Alternative Relics? The Sensory Powers of the Criminal Corpse - McIlvenna, Una (Renaissance and Reformation / Renaissance et Réforme, 2025)
Across early modern and nineteenth-century Europe it was widely believed that the corpses of executed criminals had thaumaturgical powers that could miraculously cure a range of illnesses if they were touched or ingested. This article looks at how touch was the key sense involved in how the magical powers of the corpses of the condemned could transfer to the living. It argues that these beliefs were linked to a much older belief in relics, which also require physical proximity in order to function effectively. It explores the different traditions around the use of these body parts across Europe, arguing that variations in practices were centred on differing methods of execution in different regions rather than on varying religious beliefs.